Probabilistic Assessment of Slip Rates and Their Variability Over Time of Offshore Buried Thrusts: A Case Study in the Northern Adriatic Sea - Panara, Yuri; Maesano, Francesco Emanuele; Amadori, Chiara; Fedorik, Jakub; Toscani, Giovanni; Basili, Roberto (Frontiers in Earth Science, 2021)
When sedimentation rates overtake tectonic rates, the detection of ongoing tectonic deformation signatures becomes particularly challenging. The northern Apennines orogen is one such case where a thick Plio-Pleistocene foredeep sedimentary cover blankets the fold-and-thrust belt, straddling from onshore (Po Plain) to offshore (Adriatic Sea), leading to subtle or null topo-bathymetric expression of the buried structures. The seismic activity historically recorded in the region is moderate; nonetheless, seismic sequences nearing magnitude 6 punctuated the last century, and even some small tsunamis were reported in the coastal locations following the occurrence of offshore earthquakes. In this work, we tackled the problem of assessing the potential activity of buried thrusts by analyzing a rich dataset of 2D seismic reflection profiles and wells in a sector of the Northern Apennines chain located in the near-offshore of the Adriatic Sea. This analysis enabled us to reconstruct the 3D geometry of eleven buried thrusts. We then documented the last 4 Myr slip history of four of such thrusts intersected by two high-quality regional cross-sections that were depth converted and restored. Based on eight stratigraphic horizons with well-constrained age determinations (Zanclean to Middle Pleistocene), we determined the slip and slip rates necessary to recover the observed horizon deformation. The slip rates are presented through probability density functions that consider the uncertainties derived from the horizon ages and the restoration process. Our results show that the thrust activation proceeds from the inner to the outer position in the chain. The slip history reveals an exponential reduction over time, implying decelerating slip-rates spanning three orders of magnitudes (from a few millimeters to a few hundredths of millimeters per year) with a major slip-rate change around 1.5 Ma. In agreement with previous works, these findings confirm the slip rate deceleration as a widespread behavior of the Northern Apennines thrust faults.